IgG4-related disease of the head and neck - Gontarz, Michał; Wyszyńska-Pawelec, Grażyna; Zapała, Jan (Journal of Stomatology, 2017)
IgG4-related disease is a rare immune-mediated condition characterized by fibrosis and infiltration of IgG4-positive plasma cells in a single or as a generalised condition. Clinically, IgG4-related disease may mimic malignant and inflammatory disorders. The head and neck region is overall the second most common site, followed by the pancreas. In the head and neck this condition may involve salivary glands, the orbit, lymph nodes, the thyroid gland, the upper respiratory tract and skin. Many disorders previously regarded as single-organ diseases, such as Küttner’s tumour, Mikulicz’s disease and Riedel’s thyroiditis are now regarded as IgG4-related diseases. This paper presents diagnostic criteria, clinicopathological features depending on the affected site as well as the treatment protocols. Due to insufficient awareness in the medical community the IgG4-related disease is often unrecognised, and in consequence leads to serious organ damage as a result of dense fibrosis, and may even cause death of the patient